Bail-Out TEVAR through a Branch of Four-Arm Dacron Graft for Misdeployment of a Frozen Elephant Trunk Prosthesis - Kikuchi, Yuta; Tsutsui, Masahiro; Ushioda, Ryohei; Shirasaka, Tomonori; Kamiya, Hiroyuki (International Journal of Angiology, 2022)
The frozen elephant trunk (FET) is an effective method for making the distal anastomosis more proximal and facilitating aortic remodeling in acute aortic dissection. However, misdeployment of FET to the false lumen has been reported in several cases. Such cases are usually treated with bail-out thoracic endovascular aortic repair (TEVAR) through the femoral artery or additional FET under direct vision to redirect the blood flow to the true lumen. We encountered a case of misdeployment of FET into the false lumen during open aortic surgery for the treatment of Stanford type A acute aortic dissection. After reconstruction of the aorta and all arch vessels, we performed antegrade bail-out TEVAR through a side branch of the four-arm Dacron graft as main access using a pull-through technique through the right femoral artery, which was perfused from the true lumen. This technique, which uses a Dacron graft branch for stent graft access, enabled us to confirm the true lumen because the distal anastomotic site was definitely the true lumen, and we were also able to avoid access difficulties at the iliac artery.
Keywords: frozen elephant trunk; bail-out thoracic endovascular aortic repair; side branch of four-arm dacron graft; pull-through technique